High Rates of Recurrent Biliary Tract Obstruction in Children with Sickle Cell Disease - Amoako, Martha O. (2012)
BACKGROUND: Individuals with sickle cell disease (SCD) have an increased risk of cholelithiasis from bilirubin stones. Symptomatic biliary tract disease (BTD) includes acute and chronic cholecystitis, obstruction of the common bile duct (CBD), cholangitis, and gallstone pancreatitis. Cholecystectomy is the main treatment strategy for symptomatic patients; however, the prevalence of recurrent BTD following cholecystectomy has not been systematically evaluated. We conducted a retrospective cohort study to describe the recurrence of BTD after cholecystectomy and characterize risk factors for recurrent disease. PROCEDURE: We identified patients <22 years of age who presented to the Johns Hopkins Children Center with symptomatic BTD from July 1993 to June 2008. RESULTS: We identified 56 patients with a total of 76 episodes of symptomatic BTD (median age at first event 15.9, range 4.6 to 21.5 years). Eleven of the 56 patients (19.6%) had at least one episode of recurrent symptomatic BTD (median follow-up of 5.3 years). Baseline characteristics were similar between the patients with a single episode of BTD and those with recurrent BTD. CONCLUSIONS: These results demonstrate that recurrent BTD is a frequent complication of SCD (20% by age 4 years) and often presents as CBD obstruction by stone, despite cholecystectomy. In our cohort, recurrence was not associated with age at first episode, baseline total bilirubin, gender, or genotype of SCD.